Dying on Airbnb: Digital infrastructures and deadly spaces. Issue 3 (27th May 2022) - Munn, Luke
Abstract: This paper uses two deaths on the accommodation platform Airbnb to consider how the spatial understandings of digital infrastructures can have consequences for mortality. The platform internalizes each home or room as a Listing, a template of variables minimally describing space as a unit of accommodation. This universal schema facilitates both compatibility and scalability. But this generic understanding ignores both the unpredictable agency of matter and the significance of a space's sociocultural past. Thus, while acknowledging the force exerted by digital infrastructures in reconfiguring the political economies of space at a global level, this Perspective paper argues that space is not adequately apprehended unless its material and historical aspects are accounted for. The paper concludes by returning to mortality in a broad sense, questioning whether digital infrastructures support or inhibit our capacities for living.